CLASSICAL THEORY TEST: ANALYSIS OF HIGH ORDER THINKING SKILLS INSTRUMENT TEST - Anggraeni, Agnes Dwi; Hermanto, Febrika Yogie (Universitas Negeri Surabaya, 2024)
Phenomenon/Issue: The issue addressed in the research is the need to add a bank of HOTS (Higher Order Thinking Skills) test instruments to the elements of simple financial management for the MPLB class XI SMK major. Purpose: The purpose of the research is to develop a bank of HOTS test instruments to assess students' abilities in simple financial management for the MPLB class XI SMK major. Novelty: The novelty of the research lies in the development of a test instrument that incorporates HOTS criteria, which aims to improve and familiarize students with higher-level thinking skills when solving tasks and problems, preparing them for both school and work in the industry. Research Methods: The research uses the 4D development model (definition, design, development, and dissemination) and employs Classical Test Theory (CTT) for analysis, including validity, reliability, discriminating power, level of difficulty, and distractor effectiveness. Results: The results showed that 30 out of 40 test items were valid, with a reliability of 0.805 (Cronbach's Alpha). Discriminating power was good for 22 items and fairly good for 8 items. All test items were effective in distracting students from the correct answers, meeting the criteria for validity, reliability, and effectiveness in assessing students' abilities. Research Contributions: The research contributes by providing a set of HOTS test instruments that can measure students' abilities in learning outcomes. The instruments are designed to enhance students' higher-level thinking skills, which are beneficial for their studies in school and future work in the industry.